Represented but unequal: The contingent effect of legal representation in removal proceedings. Issue 4 (6th December 2021) - Ryo, Emily; Peacock, Ian
Abstract: Substantial research and policymaking have focused on the importance of lawyers in ensuring access to civil justice. But do lawyers matter more in cases decided by certain types of judges than others? Do lawyers matter more in certain political, legal, and organizational contexts than others? We explore these questions by investigating removal proceedings in the United States—a court process in which immigration judges decide whether to admit noncitizens into the United States or deport them. Drawing on over 1.9 million removal proceedings decided between 1998 and 2020, we examine whether the representation effect (the increased probability of a favorable outcome associated with legal representation) depends on judge characteristics and contextual factors. We find that the representation effect is larger among female (than male) judges and among more experienced judges. In addition, the representation effect is larger during Democratic presidential administrations, in immigration courts located in the Ninth Circuit, and in times of increasing caseload. These findings suggest that the representation effect depends on who the judge is and their decisional environment, and that increasing noncitzens' access to counsel—even of high quality—might be insufficient under current circumstances to ensure fair and consistent outcomes in immigration courts.